2019
DOI: 10.1007/s13205-019-1714-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profiling analysis of NBS–LRR genes involved in Fusarium oxysporum f.sp. conglutinans resistance in cabbage

Abstract: As one of the most important resistance (R) gene families in plants, the NBS-LRR genes, encoding proteins with nucleotidebinding site (NBS) and leucine-rich repeat (LRR) domains, play significant roles in resisting pathogens. The published genomic data for cabbage (Brassica oleracea L.) provide valuable data to identify and characterize the genomic organization of cabbage NBS-LRR genes. Ultimately, we identified 105 TIR (N-terminal Toll/interleukin-1 receptor)-NBS-LRR (TNL) genes and 33 CC (coiled-coil)-NBS-LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…This difference between gene types may be due to the conservative nature of CNL gene replications, which involve many regulatory components. This result is also consistent with those reported for A. thaliana, B. rapa, and B. oleracea [17,20,35]. Although the TNL and CNL genes are related to signaling and resistance speci city during pathogen recognition, the genes in these two subfamilies vary regarding sequences and associated signaling pathways and they cluster separately according to phylogenetic analyses [44].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This difference between gene types may be due to the conservative nature of CNL gene replications, which involve many regulatory components. This result is also consistent with those reported for A. thaliana, B. rapa, and B. oleracea [17,20,35]. Although the TNL and CNL genes are related to signaling and resistance speci city during pathogen recognition, the genes in these two subfamilies vary regarding sequences and associated signaling pathways and they cluster separately according to phylogenetic analyses [44].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, with a focus on the NBS-LRR genes, we examined the encoded conserved domains as well as phylogenetic relationships and synteny with genes from A. thaliana, B. rapa, and B. oleracea. Furthermore, the pathogen-induced NBS-LRR gene expression pro les indicated that some R genes are highly expressed in various genetic backgrounds [35]. Our results provide crucial insights into the evolution of this gene family in the radish genome.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations